Impact of Long-Term Dienogest Therapy on Quality of Life in Asian Women with Endometriosis: the Prospective Non-Interventional Study ENVISIOeN - Techatraisak K. (2023)
Several clinical trials in women with endometriosis demonstrated that dienogest reduces endometrial lesions and improves health-related quality of life (HRQoL). To assess HRQoL in dienogest-treated patients in real-world setting, we conducted a prospective, non-interventional study in 6 Asian countries. Women aged ≥18 years with clinical or surgical diagnosis of endometriosis, presence of endometriosis-associated pelvic pain (EAPP) and initiating dienogest therapy were enrolled. The primary objective was to evaluate HRQoL using the Endometriosis Health Profile-30 (EHP-30) questionnaire. The secondary objectives included analysis of EAPP, satisfaction with dienogest, endometriosis symptoms and bleeding patterns. 887 patients started dienogest therapy. Scores for all EHP-30 scales improved with the largest mean changes at month 6 and 24 in scale pain (−28.9 ± 27.5 and − 34 ± 28.4) and control and powerlessness (−23.7 ± 28.2 and − 28.5 ± 26.2). Mean EAPP score change was −4.6 ± 3.0 for both month 6 and 24 assessments. EAPP decrease was similar in surgically and only clinically diagnosed patients. From baseline to month 24, rates of normal bleeding decreased (from 85.8% to 17.5%) while rates of amenorrhea increased (from 3.5% to 70.8%). Majority of patients and physicians were satisfied with dienogest. Over 80% of patients reported symptoms improvement. 39.9% of patients had drug-related treatment-emergent adverse events, including vaginal hemorrhage (10.4%), metrorrhagia (7.3%) and amenorrhea (6.4%). In conclusion, dienogest improves HRQoL and EAPP in the real-world setting in women with either clinical or surgical diagnosis of endometriosis. Dienogest might be a promising first-line treatment option for the long-term management of debilitating endometriosis-associated symptoms. NCT02425462, 24 April 2015.